2019
DOI: 10.1007/s00259-019-04397-2
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and preclinical characterization of [18F]PI-2620, a next-generation tau PET tracer for the assessment of tau pathology in Alzheimer’s disease and other tauopathies

Abstract: Purpose Tau deposition is a key pathological feature of Alzheimer’s disease (AD) and other neurodegenerative disorders. The spreading of tau neurofibrillary tangles across defined brain regions corresponds to the observed level of cognitive decline in AD. Positron-emission tomography (PET) has proved to be an important tool for the detection of amyloid-beta (Aβ) aggregates in the brain, and is currently being explored for detection of pathological misfolded tau in AD and other non-AD tauopathies. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
185
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 170 publications
(218 citation statements)
references
References 40 publications
17
185
2
1
Order By: Relevance
“…In autoradiography studies it also showed to tau aggregates/folds in PSP brain sections, which of course has been controversial, since many tau tracers has been reported not to be bind to tau deposits in PSP in autoradiography experiments. However, off-target binding was observed in the pars compacta portion of the substantia nigra in human brain sections, consistent with the affinity of some tau tracers like flortaucipir, [ 18 F]MK-6240 to melanin-containing cells [52,53,201].…”
Section: Optimized First Generation Tau Tracerssupporting
confidence: 67%
“…In autoradiography studies it also showed to tau aggregates/folds in PSP brain sections, which of course has been controversial, since many tau tracers has been reported not to be bind to tau deposits in PSP in autoradiography experiments. However, off-target binding was observed in the pars compacta portion of the substantia nigra in human brain sections, consistent with the affinity of some tau tracers like flortaucipir, [ 18 F]MK-6240 to melanin-containing cells [52,53,201].…”
Section: Optimized First Generation Tau Tracerssupporting
confidence: 67%
“…One AD subject who was in a very mild stage of the disease demonstrated no uptake. faced by tau tracers from prior generations, was also demonstrated (Kroth et al, 2019;Stephens et al, 2018 ommended for further investigation as minimal binding was found in controls and patients with AD had region-specific patterns of tracer uptake consistent with pathohistological data for the spread of tau pathology (Wong et al, 2018). Not only does [ 18 F]GTP1 retention correspond to established patterns of brain tau distribution in AD, but this new second-generation tau tracer was also correlated with performance on cognitive measures, particularly in the earliest stages of AD (Bohórquez et al, 2019;Teng et al, 2018;Teng et al, 2019).…”
Section: Second-generation Tau Tracersmentioning
confidence: 81%
“…In two AD subjects in advanced disease stages, uptake was also found in neocortical temporal, frontal, and parietal areas. Kroth et al (2019) [ 18 F]PI-2620 Four AD patients, two healthy controls Three AD subjects showed asymmetric distributions of tracer retention in temporal regions, the precuneus, and post-cingulate. One AD subject who was in a very mild stage of the disease demonstrated no uptake.…”
Section: Second-generation Tau Tracersmentioning
confidence: 99%
“…This designates tauopathy an important target for early diagnostic and therapeutic intervention for Alzheimer's disease, FTLD, and other tauopathy disorders [6]. Tau tracers for positron emission tomography (PET) have been developed recently [5,[7][8][9][10][11][12], while tau imaging has emerged as a useful tool for disease staging, progression prediction, treatment stratification, and monitoring in clinical research setting.…”
Section: Introductionmentioning
confidence: 99%
“…Whole brain highresolution tau imaging in these disease models provide insights for mechanistic and therapeutic studies [18,19]. At macroscopic level, in vivo imaging of tauopathy was enabled by PET in P301L mouse line using 11 C-PBB3 [20][21][22] or 18 F-PI-2620 [10] tau probes. However, the limited resolution of microPET (1 mm) relative to the mouse brain (~10 mm 3 ) and the need for dedicated and expensive infrastructure for radiolabeling limit usability in preclinical setting.…”
Section: Introductionmentioning
confidence: 99%